How not to propose to a duke - Allen, Louise (Harlequin historicals., 2024)
Miss Danby’s daring proposition for the duke : First, wealthy ironmaster’s daughter Jessica Danby needs a titled husband. So, upon learning that Alexander, the Duke of Malvern, needs a rich wife, she makes a convenient proposal… Next, her impetuous marriage offer is swiftly rejected by Alex, who wants to marry for love! Now Jessica accepts his help in finding another suitor. But as they spend the Season by each other’s side, she realizes that their unlikely friendship is becoming something more thrilling!